Urbanisation in developing economies: Building cities that work - Venables, AJ (European Regional Science Association, 2018)
This paper reviews recent work on the economics of fast growing developing country cities, with a focus on Africa. It sets out some of the broad facts about African urbanisation and summarises two recent pieces of research work. The first argues that coordination failure can create multiple equilibria and divergent paths of development, some in which cities are internationally competitive and able to create jobs, others in which cities are stuck in a ‘nono-tradables trap’. The second is a dynamic model of city growth, calibrated to changing patterns of land-use in Nairobi; the calibration suggests a very high cost of inefficient land use in the context of urban slums.